2013
DOI: 10.14295/rbho.v19i1.423
|View full text |Cite
|
Sign up to set email alerts
|

Análise quali - quantitativa da vegetação e dos elementos arquitetônicos da Praça Dom Assis, Jaboticabal, São Paulo

Abstract: As praças são espaços públicos urbanos livres de edificações e que propiciam convivência e recreação para seus usuários, além de contribuírem para o embelezamento das cidades, desempenhando uma função importante no contexto urbanístico ambiental. Tendo em vista a importância das praças e as conseqüências do crescimento urbano, este trabalho teve como objetivo avaliar a situação atual e usos da Praça Dom Assis de Jaboticabal, mediante análise quali-quantitativa da vegetação e dos elementos arquitetônicos e uma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The arboreal composition of squares' landscape has been described in several Brazilian regions (Batista et al, 2013;Tischer et al, 2014;Gomes et al, 2016). José Bonifácio Square shows a large diversity of trees implemented on the historic square.…”
Section: The Arboreal Composition and Ecological Importance Of José Bonifácio Squarementioning
confidence: 99%
See 1 more Smart Citation
“…The arboreal composition of squares' landscape has been described in several Brazilian regions (Batista et al, 2013;Tischer et al, 2014;Gomes et al, 2016). José Bonifácio Square shows a large diversity of trees implemented on the historic square.…”
Section: The Arboreal Composition and Ecological Importance Of José Bonifácio Squarementioning
confidence: 99%
“…The author concluded that the square's arboreal composition might be considered an ecological fragility (Romani et al, 2012). Batista et al (2013) observed a value that reached 15.7% of the frequency of Caesalpinia peltophoroides specie known as Sibipiruna (Momoqui) at Dom Assis Square in Jaboticabal, São Paulo. Therefore, the author highlighted the importance of urban planning for urban spaces landscaping as a tool for avoiding several diversity-related failures.…”
Section: The Arboreal Composition and Ecological Importance Of José Bonifácio Squarementioning
confidence: 99%